Bio-Compatible Processing of LENSTM DepositedCo-Cr-W alloy for Medical Applications - Suresh, Ganzi; L Narayana, K; Kedar Mallik, M (International Journal of Engineering and Technology, 2018)
Developing a Medicinal implants or devices is a challenging task for the researchers, right from the selection of materials, design, bio-compatibility and implantation to the host tissue. At every stage it requires proper care in processing of medical implants. In recent years the demand for medical implants had grown rapidly due to the awareness in the society. Major share of implants is used by younger people as they are active in sports, motor vehicle accidents leads to facture. Even older people also preferring to implants for ease of living. The commonly used implants are, prosthetic joints, knee replacement, dental, maxillofacial reconstructions etc.There is huge demand for the medical implants in coming years, presently a few bio-materials available for implant devices such as Ti-alloys, Stainless steel and Co-Cr-Mo alloys. There a scope to the researchers to develop a new alloy that are bio-compatible in nature and bring down the cost of the implant procedure to the needed patients. In this context additive manufacturing (AM) is an advanced manufacturing technology emerging as prominent technique in medical fields. Laser Engineered Net ShapingTM (LENS) is one such metal additive technique which provides fabrication of parts with the help of laser power, melts the powder alloy completely and builds parts layer by layer directly from the CAD model.In the present study, samples are fabricated from LENS process and carried the In-Vitro and In -Vivo bio-compatible tests as cytotoxicity and sub chronic toxicity to verify the toxicants release and their sustainability as the medical implants by the LENS deposited Co-Cr-W alloy samples. From the studies it is observed that the alloy samples show acceptable result. MTT assay demonstrate that cell viability is better in Osteoblast cells compared to the Fibroblast cells. Osteoblast cells show slightly more viable to the cell treatment on the samples during the experimental period. Sub chronic toxicity conclude that LENS deposited Co-Cr-W alloy is not toxic in all the rats studied herein and did not produce any toxic signs or evident symptoms. LENS deposited Co-Cr-W alloy did not cause any lethality or produce any relative body organs weight and haematological studies didnâ€™t show adverse effects.Â Â